Cultural Studies: A Space for Education - Worrell, Patricia (Daily Express, 2004)
This article examines the importance of Cultural Studies to education in the Caribbean. It notes that Cultural Studies has a significant role to play in helping educators to understand some of the cultural phenomena that have helped to silence Caribbean students and make their school experience "inhumane," and in proposing models of education to address the urgent problems identified
Keywords: Cultural Studies; Education and culture; Caribbean